ANALYSIS OF THE EFFECT OF LIQUIDITY RATIOS, SOLVABILITY RATIOS AND PROFITABILITY RATIOS ON FIRM VALUE IN GO PUBLIC COMPANIES IN THE AUTOMOTIVE AND COMPONENT SECTORS - Suhesti Ningsih; Shinta Permata Sari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
The research objective to be achieved in this study is to determine the effect of financial ratios on firm value in publicly listed companies in the automotive and component sub-sectors. The financial ratios used for analysis are the current ratio (CR), debt to total asset ratio (DAR) and return on assets (ROA). To measure the value is the price to book value (PBV). The method of analysis in this study is quantitative data analysis, to quantitatively estimate the effect of independent variables simultaneously (together) or partially (individually) on the dependent variable. From the results of the partial analysis test, the results show that CR and DAR do not affect the value of the company in automotive and component companies because it has a significance value greater than 0.05, 0.0875 and 0.084. While ROA has a significance value of 0.00> 0.05, this means that ROA affects the firm's value. Simultaneous test results show that jointly affect the value of the company in automotive and component companies, this is evidenced by the value of F has a coefficient of 0,000. Keyword : Current Ratio, debt to total asset ratio, return on Assets, price to book value.